Active forces modulate collective behaviour and cellular organization Des forces actives modulent le comportement collectif et l'organisation cellulaire - Balasubramaniam, Lakshmi; Mège, René Marc; Ladoux, Benoit (Comptes Rendus Biologies, 2021)
Biological tissues are composed of various cell types working cooperatively to performtheir respective function within organs and the whole body. During development, embryogenesis followed by histogenesis relies on orchestrated division, death, differentiation and collective movements of cellular constituents. These cells are anchored to each other and/or the underlying substrate through adhesion complexes and they regulate force generation by active cytoskeleton remodeling. The resulting changes in contractility at the level of each single cell impact tissue architecture and remodeling by triggering changes in cell shape, cell movement and remodeling of the surrounding environment. These out of equilibrium processes occur through cellular energy consumption, allowing biological systems to be described by active matter physics. Cytoskeleton filaments, bacterial and eukaryotic cells can be considered as a sub-class of active matter termed "active nematics". These biological objects can be modelled as rod-like elements to which nematic liquid crystal theories can be applied. In this work, using an analogy from liquid crystal physics, we show that cell sorting and boundary formation can be explained using differences in nematic activity. This difference in nematic activity arises from a balance of inter- and intra-cellular activity.
CRIS-Team Scopus Importer:2024-02-19
Keywords: Active nematics; Cell segregation; Cytosquelette/ cytoskeleton; Mechanobiology; Topological defects